Smart green zones: Review - Khazaal, Ruqayah Basim; Neima, Saba Jabbar; Musa, Abeer Ibrahim (Edelweiss Applied Science and Technology, 2024)
Managing green spaces to become smart is an important factor, so the research focused on identifying the knowledge gap on how to manage smart green spaces. The importance of smart management techniques that rely on sensors, the Internet, and artificial intelligence in providing data for decision-making is highlighted, to enhance the life quality within green spaces and enhance their sustainability by adopting technology data to maintain and manage green zones. Despite the importance of green zones and their multiple benefits, many cities face significant challenges in managing them effectively and sustainably. These challenges vary between the lack of material and human resources, plant conservation problems and green infrastructure, as well as the unpredictability of future environmental needs. The research relied on investigating the concept of smart green zones, their characteristics, smart management concept, strategies and application to study situations to find ways and means of intelligently conserving and managing natural resources. The research recommends the need to strengthen studies and research and community participation in order to enhance the quality of green zones through technological development.